Scientists-sytenkivtsi. yuriy yuliyovych kolontay (on the 90th anniversary of his birth) - Loskutov, Oleksandr; Naumenko, Leonid (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The article is devoted to the 90 anniversary since the birth of the outstanding scientist Yuri Yulievich the Kolontai.